Intention to engage in inter-contractor cooperation: A belief elicitation study in the construction industry - Moshood, Taofeeq D.; Ling, Yee Voon; Chai, Changsaar; Lee, Chia Kuang (Emerald, 2024)
Purpose: Partnering has been introduced to the construction field to improve project delivery efficiency. However, little research outlines the factors influencing the intention to form partnerships. This paper aims to investigate the relationships between attitude, subjective norm perceived behavioural control (PBC) and intention to form partnering, as well as to elicit behavioural, normative and control beliefs regarding partnering formation. The study also examines the relationships between these beliefs and their respective constructs within the Theory of Planned Behavior (TPB) framework. Design/methodology/approach: In order to achieve these objectives, a two-stage approach was employed. First, a belief elicitation study (BES) involving 20 construction industry professionals was conducted to elicit salient beliefs. Subsequently, a TPB survey was administered to 99 contractors from grades G4 to G7. Partial Least Square analysis assessed the factors influencing the intention to form partnering. Findings: The results supported six hypotheses, while six others were unsupported. Perceived usefulness significantly influenced attitude towards intention to form partnering, followed by attitude itself, which also significantly influenced intention. The project management team and sole proprietors had significant effects on the subjective norms, while facilitating conditions and consensus on appropriation significantly affected PBC. Practical implications: This research contributes to the existing literature by providing empirical evidence on the role of intention in partnering formation. Moreover, by applying the BES, this research extends the TPB model of intention to form partnering in construction projects, offering valuable insights for future research and practice. Originality/value: This study investigates the relationships between attitude, subjective norm PBC and intention to form partnering, as well as to elicit behavioural, normative and control beliefs regarding partnering formation. The study also examines the relationships between these beliefs and their respective constructs within the TPB framework.